L’étrange héritage des conversation pieces chez Stanley Spencer : du XVIIIe siècle au XXe siècle - Liliane Louvel (Interfaces)
Stanley Spencer, R.A. is famous for his Resurrections, his strange series inspired by sacred texts and for the Burghclere Memorial’s « frescoes » among other pieces. His work also reveals a taste for portraiture. Some of his works are seemingly in line with conversation pieces, this 18th-century family portrait genre which contributed to establish British identity. S. Spencer has often been hailed as an English painter, in particular thanks to his celebration of the rural landscapes of his native Berkshire and of his beloved Cookham. Some of his portraits seem to display pictorial elements reminiscent of the genre, focussing on small groups of people standing or sitting in their familiar surroundings. The portraits of influential people like those of Dr Osmund Frank, the Mayor of Maidenhead and his wife, of J.E. Martineau or of J. L. Berhend, his friends and commissioners are all sitting in private rooms. Mr and Mrs Baggett’s portrait opens onto a window overlooking the churchyard, one of Spencer’s favourite motifs. This unusual disposition evokes one of G. Romney’s works, Mr and Mrs William Lindow (1772). This paper will propose a close study of the presence of his English heritage in the work of such an eccentric and often baffling painter.